2021
DOI: 10.3390/su131911080
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Drivers for Circular Economy 2.0 on the Firm Level: Russian Case

Abstract: Historically, the development of the circular economy (CE) proceeds from the CE 1.0 stage, characterized by attention to waste management and recycling, to the CE 2.0 stage with an emphasis on resource efficiency and eco-efficiency, to the current CE 3.0 stage, in which the key factor to a company’s success is the business model. However, not all countries of the world simultaneously began transforming the national economy from a linear model to a circular one; many are still at the CE 1.0 and CE 2.0 stages, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…However, the USA does not have a similar legal framework (EPA, 2021). As another example, Ratner et al (2021) point out the lack of the macro-level policy frameworks as an important reason behind why the Russian firms lag behind the EU firms in performing circular actions. In this regard, Cantú et al (2021) also argue that the poor regulative power of the emerging countries compared to the developed countries is an important structural reason for the SMEs in the emerging countries lagging behind the ones in the developed countries.…”
Section: The Findings and Further Discussionmentioning
confidence: 99%
“…However, the USA does not have a similar legal framework (EPA, 2021). As another example, Ratner et al (2021) point out the lack of the macro-level policy frameworks as an important reason behind why the Russian firms lag behind the EU firms in performing circular actions. In this regard, Cantú et al (2021) also argue that the poor regulative power of the emerging countries compared to the developed countries is an important structural reason for the SMEs in the emerging countries lagging behind the ones in the developed countries.…”
Section: The Findings and Further Discussionmentioning
confidence: 99%
“…Most implementation projects result in higher production costs due to limited demand for resource-efficient goods and services. Russian firms' primary obstacles to implementing CE include complex administrative and regulatory procedures and high costs associated with resource efficiency projects [29]. Moreover, the ongoing conflict between Russia and Ukraine may further hinder the implementation of such measures.…”
Section: The Ecological Impact Of Drivetrain Components Considering T...mentioning
confidence: 99%
“…For instance, Ratner et al. [ 34 ] clustered companies from several EU countries and Russia according to their institutional support system. Botezat et al.…”
Section: Prior Research On Circular Economy Measures and Profilesmentioning
confidence: 99%
“…Several studies have identified CE profiles, ranging from the firm to the country level. For instance, Ratner et al [34] clustered companies from several EU countries and Russia according to their institutional support system. Botezat et al [35] performed a cluster analysis of Romanian companies based on their level of green-oriented supply chain cooperation practices.…”
Section: Prior Research On Circular Economy Measures and Profilesmentioning
confidence: 99%